An assessment of the level of job satisfaction among faculty members in a Philippine University - de Guzman, Renen Szilardo C.; Depositario, Dinah Pura T.; Banzon, Agnes T. (2019)
An assessment of levels of satisfaction was conducted among 142 faculty members of a Philippine university. In general, the members of the faculty were satisfied with their jobs. These were due to the personal and professional growth and development, as well as the freedom and flexibility the job has provided them to achieve work-life balance. Though, administrative functions such as promotion, document processing, salary and benefits, and university facilities were evaluated to be relatively less satisfactory. Using regression analysis, it was determined that years of service, gender, number of course preparations, work fulfillment, safety, salary contentment, and career advancement significantly contribute to satisfaction. Further, utilizing factor analysis, six relevant factors related to job satisfaction were identified; workload, social and societal interactions, growth and development, compensation and benefits, administration, and classroom experience. Satisfaction was seen to have moderate and weak positive relationship with organizational citizenship and intent to continue work, respectively. It is recommended that the university should continue creating an environment conducive for personal and professional growth and development through its plans and programs. The insights the research provided call for more efficient document processing through automation and computerization, thorough review and revision of promotion policies and procedures, and improvements in infrastructure.
Keywords: Job satisfaction; University faculty; Human Resource Management (HRM)